NF-B1 Rs28362491 Mutant Allele Frequencies Along the Silk Road and Beyond - Safoora PORDEL; Kazem NEMATI; Mohammad Hossein KARIMI; Mehrnoosh DOROUDCHI (Tehran University of Medical Sciences, 2018)
Background: In the human evolutionary history, Single Nucleotide Polymorphism (SNP) frequencies are valuable in terms of finding connections between different populations. Due to the pronounced role of the immune system in combating pathogens and environmental stressors, polymorphisms in the immune genes are subject to selection pressure of the diseases as well. The functional polymorphisms in NF-kB1 promoter (-94 ins/del) are associated with different diseases; therefore, we aimed to establish the frequencies of NF-kB1 rs28362491 alleles in a population of Southwestern Iranians in comparison with the world populations. Methods: We assessed the polymorphism of -94 ATTG ins/del (rs28362491) in 201 Iranian healthy blood donors from Fars Province, central Iran in a one year period between 2015 and 2016 by PCR-RFLP method using DNA extracted from peripheral blood mononuclear cells. Results: The frequency of ins/ins homozygote genotype was found to be 46.97%. The frequency of heterozygote individuals was 42.42% and the percentage of del/del homozygote genotype was 10.61%. We observed a genetic similarity based on the genotype frequencies of NF-kB1 -94 ins/del ATTG polymorphism between our sample of Iranians with American Jewish, Turkish, American non-Jewish, Chinese-Uyghurs and Germans. Conclusion: The results confirmed genetic interrelation of Iranians with some ancient neighbors and their admixture with countries along the Silk Road. We suggest that mapping the distribution of NF-kB1-94 ATTG ins/del along with HLA genes may help to better define the relations between human populations and design population-specific vaccines for pathogens with a high rate of variation.